The world according to Tom Hanks : the life, the obsessions, the good deeds of America's most decent guy - Edwards, Gavin, 1968- (Grand Central Publishing, 2018)
Draws on extensive research and interviews to provide insight into the optimism and integrity in both the personal life and career of actor Tom Hanks.